Visuospatial working memory and attention control make the difference between experts, regulars and non-players of the videogame League of Legends - Valls-Serrano, Carlos; De Francisco, Cristina; Vélez-Coto, María; Caracuel, Alfonso (Frontiers in Human Neuroscience, 2022)
Video games have been postulated as an emerging field for studying the cognition-expertise relationship. Despite this, some methodological practices hinder scientific advance (e.g., heterogeneous samples, an ambiguous definition of expertise, etc.). League of Legends is a massively played video game with a well-established structure that meets the requirements to overcome current study limitations. The aim of this study was to analyze cognitive differences among expert LOL players, regular LOL players, and non-players. A sample of 80 participants was enrolled in three different groups of expertise. Participants were evaluated with behavioral tests of working memory, attention, cognitive flexibility, and inhibition. Kruskal-Wallis tests for group comparison showed that the experts performed significantly better than regular players and non-players in the working memory test. Significant differences were also found between players and non-players in the attention test. Methodological implications for future research in neuroscience and human-computer interaction are discussed.